Carbono almacenado en la biomasa de las especies comerciales del bosque de colina baja de la concesión forestal N° 16-IQU/C-J-170-04, distrito de Mazán, Loreto. 2022 - Ramos Arirama, Cindy Luisa (2023)
The biomass and carbon stored in commercial species of a low hill forest in the district of Mazán, Loreto, Peru was quantified. Data from the forest census of the commercial species of the forest concession contract N° 16-IQU/C-J-170-04 for timber purposes were evaluated. The results indicate a total dry biomass of 19 806.93 kg/ha, with Parkia ulei providing the highest biomass of 2209.27 kg/ha and Virola flexuosa 1909.17 kg/ha. The diameter class from 60 cm to 70 cm contains the highest dry biomass of 4563.27 kg/ha and from 70 cm to 80 cm of 4286.19 kg/ha. The carbon stored is 9.90 tC/ha, where Parkia ulei contributes the highest amount of 1.10 tC/ha and Virola flexuosa 0.95 tC/ha. The diameter class from 60 cm to 70 cm contains a higher carbon stock of 2.28 tC/ha and from 70 cm to 80 cm of 2.14 tC/ha. Statistically there is a significant difference (α = 0.05) between the averages of biomass and carbon stored.